The Effect Of Job Stress, Non-Physical Work Environment, And Job Satisfaction On Employee Performance At PT. Pertamina Hulu Rokan Supply Chain Management (SCM) Division, General Services Zone 4 Prabumulih - Suci Andini Fitri; Zunaidah; Wita Farla WK; M. Ichsan Hadjri (International Journal of Economics Accounting and Management, 2026)
This study was conducted to determine the analysis of the Influence of Job Stress, Non-Physical Work Environment, and Job Satisfaction on Employee Performance at PT Pertamina Hulu Rokan (PHR) Supply Chain Management (SCM) Function General Services Division Zone 4 Prabumulih. The research collection technique was with a questionnaire. The data collection technique used in the study was qualitative analysis in the form of questionnaire statements that were quantified using a Likert scale. The research population was 150 people. The sampling technique for this study used the saturated sample technique method. Data analysis techniques with Data collection using questionnaires as a research tool must meet two criteria, namely validity and reliability. Then with the classical assumption test, namely the normality test, multicollinearity test, and heteroscedasticity test. Then the correlation coefficient (r) and determination coefficient (R2) test and multiple linear regression analysis. The results of the study showed that job stress had a significant negative effect, while the non-physical work environment and job satisfaction had a significant positive effect on employee performance.